Balancing aspirations and realities: A qualitative study of L2 motivation among Sri Lankan social science lecturers in English medium instruction - Sujeewa Hettiarachchi; Chitra Jayathilake; Sujeeva Sebastian Pereira (Discover Education)
Abstract This qualitative study uses deductive thematic analysis to examine the L2 motivation of social science lecturers working in English Medium Instruction (EMI) contexts at selected Sri Lankan universities. Drawing on Dörnyei’s (Dörnyei in The psychology of the language learner, Routledge, London, 2005) L2 Motivational Self System (L2MSS) as its primary theoretical framework, it investigates how participants construct their Ideal and Ought-to L2 Selves and how these concepts intersect with their EMI teaching experiences. Data from six in-depth interviews reveal that while participants aspire to become competent academic communicators in English, the progress toward their Ideal L2 Self is hindered by structural and linguistic challenges, including limited institutional support, restricted exposure to English and low student engagement in the classroom. The Ought-to L2 Self emerges prominently in response to institutional mandates, societal expectations and the symbolic power of English in Sri Lanka. Although participants generally express a positive outlook on EMI, they also acknowledge its inequitable impact on students from under-resourced backgrounds, as well as their own linguistic and pedagogical limitations. The study offers insights into the interplay between motivation, identity and structural inequality in EMI and calls for more context-sensitive implementation strategies that balance global aspirations with local realities.